Nanotoxicology and Nanosafety: Safety-by-Design and Testing at a Glance - Zielinska, Aleksandra (2020)
This review offers a systematic discussion about nanotoxicology and nanosafety associated with nanomaterials during manufacture and further biomedical applications. A detailed introduction on nanomaterials and their most frequently uses, followed by the critical risk aspects related to regulatory uses and commercialization, is provided. Moreover, the impact of nanotoxicology in research over the last decades is discussed, together with the currently available toxicological methods in cell cultures (in vitro) and in living organisms (in vivo). A special focus is given to inorganic nanoparticles such as titanium dioxide nanoparticles (TiO2NPs) and silver nanoparticles (AgNPs). In vitro and in vivo case studies for the selected nanoparticles are discussed. The final part of this work describes the significance of nano-security for both risk assessment and environmental nanosafety. “Safety-by-Design” is defined as a starting point consisting on the implementation of the principles of drug discovery and development. The concept “Safety-by-Design” appears to be a way to “ensure safety”, but the superficiality and the lack of articulation with which it is treated still raises many doubts. Although the approach of “Safety-by-Design” to the principles of drug development has helped in the assessment of the toxicity of nanomaterials, a combination of scientific efforts is constantly urgent to ensure the consistency of methods and processes. This will ensure that the quality of nanomaterials is controlled and their safe development is promoted. Safety issues are considered strategies for discovering novel toxicological-related mechanisms still needed to be promoted.